Metal atom markers for imaging epitaxial molecular self-assembly on graphene by scanning transmission electron microscopy - Lee, JK; Bulut, I; Rickhaus, M; Sheng, Y; Li, X; Han, G; Briggs, G; Anderson, H; Warner, J (American Chemical Society, 2019)
Direct imaging of single molecules has to date been primarily achieved using scanning probe microscopy, with limited success using transmission electron microscopy due to electron beam damage and low contrast from the light elements that make up the majority of molecules. Here, we show single complex molecule interactions can be imaged using annular dark field scanning TEM (ADF-STEM) by inserting heavy metal markers of Pt atoms and detecting their positions. Using the high angle ADF-STEM Z1.7 contrast, combined with graphene as an electron transparent support, we track the 2D monolayer self-assembly of solution-deposited individual linear porphyrin hexamer (Pt-L6) molecules and reveal preferential alignment along the graphene zigzag direction. The epitaxial interactions between graphene and Pt-L6 drive a reduction in the interporphyrin distance to allow perfect commensuration with the graphene. These results demonstrate how single metal atom markers in complex molecules can be used to study large scale packing and chain bending at the single molecule level.